PENGARUH KETEPATAN PELAPORAN LAPORAN KEUANGAN, OPINI AUDIT, PERGANTIAN KANTOR AKUNTAN PUBLIK, DAN REPUTASI KANTOR AKUNTAN PUBLIK TERHADAP REAKSI INVESTOR - Roestanto Sukarta Diputra; Yane Devi Anna (Bina Ekonomi, 2014)
Investor reaction is a form of market response to information contained in an announcement issued or published. If information contains some information, then the market will respond or react quickly when the information is posted. Investors as parties are not know information about the situation in the company, investors will consider the information issued by the company as a signal used for financial decision making. This study aims to determine the effect of the accuracy of reporting financial statements, the audit opinion, the turn of the public accounting firm, and the reputation of the Public Accounting Firm of the reaction of investors to the issuer Kompas 100 2010-2012. This study is classified as descriptive research verification of causality. The population in this study is a listed company in Kompas index 100 in 2010-2012. By using purposive sampling, the samples used in this study amounted to 40 companies. The data used in this study is secondary data. The method of data analysis used panel data regression analysis. The results of this study are simultaneously, there is significant influence between the accuracy of reporting financial statements, the audit opinion, the turn of the public accounting firm, and the reputation of the Public Accounting Firm of the reaction of investors. It can be concluded that the public accounting firm's reputation has a significant influence on the reaction of investors, while the reporting accuracy of the financial statements, the audit opinion, and turn public accounting firm did not have a significant effect on investor reaction.